A recurrent translocation is mediated by homologous recombination between HERV-H elements - Hermetz Karen E; Surti Urvashi; Cody Jannine D; Rudd M Katharine (Molecular Cytogenetics, 2012)
Abstract Background Chromosome rearrangements are caused by many mutational mechanisms; of these, recurrent rearrangements can be particularly informative for teasing apart DNA sequence-specific factors. Some recurrent translocations are mediated by homologous recombination between large blocks of segmental duplications on different chromosomes. Here we describe a recurrent unbalanced translocation casued by recombination between shorter homologous regions on chromosomes 4 and 18 in two unrelated children with intellectual disability. Results Array CGH resolved the breakpoints of the 6.97-Megabase (Mb) loss of 18q and the 7.30-Mb gain of 4q. Sequencing across the translocation breakpoints revealed that both translocations occurred between 92%-identical human endogenous retrovirus (HERV) elements in the same orientation on chromosomes 4 and 18. In addition, we find sequence variation in the chromosome 4 HERV that makes one allele more like the chromosome 18 HERV. Conclusions Homologous recombination between HERVs on the same chromosome is known to cause chromosome deletions, but this is the first report of interchromosomal HERV-HERV recombination leading to a translocation. It is possible that normal sequence variation in substrates of non-allelic homologous recombination (NAHR) affects the alignment of recombining segments and influences the propensity to chromosome rearrangement.